Comparison among the Turbulence Models to Simulate Flow Pattern over ogee Spillway Case Study (Mandali dam in Iraq) - ., Ahmed Imad Rajaa; ., Ammar Hatem Kamel (Iraqi Journal of Civil Engineering, 2022)
The spillway is an important structure in the dams, used to pass the flood wave to the downstream safely. In the past decades, Computational fluid dynamics (CFD) has evolved. Research findings have shown the CFD models are a great alternative for laboratory models. According to it, the flow pattern over ogee spillways can be studied in a short time and without paying high expenses. Because the flow over the ogee spillway is turbulent and has a free surface, its properties are complex and often difficult to predict. Therefore, the present paper focuses on the study of turbulence closure models including the standard k-ε, RNG k–ε, k–ω, also, the large-eddy simulation (LES) models, to assess their performance to simulate flow over the spillway. The Flow-3d software with the volume-of-fluid (VOF) algorithm is applied to obtain the free surface for each turbulence model. The results of the analysis show that the LES model yielded better results when compared with laboratory results, while the turbulence closure models result of Reynold average Navier Stocks equations (RANS) was more stable, especially standard k-ɛ and RNG models.